Moyamoya disease in a pediatric case: A case report - Bulut, Hacı Taner; Çoraplı, Mahmut (Journal of Surgery and Medicine, 2022)
Moyamoya disease is extremely rare. In children, it is one of the rare causes of ischemic stroke. We present a 4-year-old female patient diagnosed with Magnetic Resonance Imaging (MRI) and Magnetic Resonance Angiography (MRA). In the case with chronic lacunar infarct in the white matter on magnetic resonance imaging, a cigarette smoke image characterized by diffuse collateral vascular networks was observed in MRA imaging. Since it is rare, we think that MRI and MRA imaging is safe and contributes to the diagnosis of the disease in children with mental and motor development retardation.